Epidemiological burden of meningococcal disease in Brazil: A systematic literature review and database analysis. (March 2019) - Presa, Jéssica Vespa; de Almeida, Rodrigo Sini; Spinardi, Júlia Regazzini; Cane, Alejandro
Highlights: Results from the literature review and Brazilian databases were found to be similar and consistent. Serogroup C is prevalent in all Brazilian regions. Brazil has presented a rise in serogroups B (up to 5 years of age) and W (young adults). Despite the reduction in reported cases, the case fatality rate (CFR) related to invasive meningococcal disease remained stable. The highest CFR seems to be associated with serogroup W. Abstract: Objectives: The aim of this study was to evaluate the epidemiological profile of invasive meningococcal disease (IMD) in Brazil, the first Latin American country to introduce the group C meningococcal conjugate vaccine (included in the vaccination schedule in 2010). Methods: A systematic review was conducted, covering the years 2005–2017, to identify epidemiological information on IMD and Neisseria meningitidis carriers in Brazil. Documents from the Brazilian Ministry of Health and two public databases were analyzed to determine annual incidence rates, absolute numbers of diagnosed cases, serogroups identified, the relative distribution of cases per serogroup, and the case fatality rate (CFR). Results: Sixteen studies were selected. The incidence rate ranged from 0.88 to 5.3 cases per 100 000 inhabitants per year. According to secondary data, the annual incidence of IMD in 2015 was highest in males <1 year old (7.1/100 000). The number of diagnosed cases declined significantly over the years. In the literature, IMD showed a CFR from 20.0% to 50.0%, and a higher CFR for serogroup W (17.8%). Secondary data showed an absolute reduction in meningitis-attributable deaths between 2007 and 2015; however, the CFR remained stable (11.1% in 2007 and 8.4% in 2015). In 2015, serogroup W showed the highest CFR (24.1%), followed by serogroups C (19.2%), B (17.7%), and Y (14.3%). Conclusions: Despite a reduction in cases, the CFR remained stable and similar in the different age groups, even for disease caused by different serogroups. The highest CFR was found to be associated with serogroup W.